A Compendium On Edge Computing Where Ai Can Meet (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Edge computing, which seems to be the latest computer framework in which information is stored on board, is the gateway to the proliferation of the internet of things and the potential to capture, interpret, and deliver huge information in the cloud. Edge Computing has gained interest in the last 2 years and has strategic implications as being among the best competitive advances in technology. It has less network performance, lower network costs, and better confidentiality security than cloud services. Edge computing contrasts cloud computing by providing computing capabilities that allow incredibly huge amounts of information from IoT devices to be processed and smart decisions need to be made. In general, automated computation is quickly implemented in artificial intelligence technology. The very first focuses on providing more efficient and popular AI technologies to optimize techniques for main problems in Edge Computing since the second discusses how its entire process of AI creation methods, i.e., model creation and expertise, is to become a part of the framework. In this paper, we suggest concepts, histories, and advantages of edge computing, demonstrate what happens and structures hierarchical structures, identify examples of its applications in various fields, and subsequent mainly improvements, and discuss the challenges of its use in 3 reflecting areas of technology.